System Analysis in the Investment Processes Management and Theoretical Principles of the Investments Assessment - AKIMOVA, Elena Mihailovna; STEIN, Elena Mihailovna; PROKHOROVA, Yulia Sergeevna (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The article is devoted to the need of application of the system analysis within the development of information systems, its principles, purposes, and as well as the stages with the description of the functions at each stage. During the definition and solution of a set of tasks the investment processes management faces the need of the analytical justification of financial, investment and operational decisions which are made at the same time and can be solved by the means of the application of the system analysis. The purpose of the investment analysis consists of: the objective assessment of the requirement, opportunity, scale, desirability, profitability and safety of the implementation of any short-term and long-term investments; the definition of the directions of investment development of the company and the priority areas of effective capital investments; the development of the acceptable conditions and the basic reference points of the investment policy; the operating identification of the factors determining the emergence of deviations of the actual investment results from the results planned earlier, and of justification of optimum investment decisions. The justification of features and general organizational and methodical approaches given in the article allows discussing the division of the investment analysis into two interconnected directions of the research: they are the analysis of capital investments (long-term investments) and the analysis of financial investments. The indicators of economic efficiency are proved to be in the rigidly determined dependence the on qualitative and quantitative parameters of a project cash flow.